Attenuated total reflectance infrared spectroscopy: A powerful method for the simultaneous study of structure and spatial orientation of lipids and membrane proteins - Ausili, A. (2017)
One of the most powerful techniques used to gain structural information of membrane proteins is the Attenuated Total Reflectance Fourier Transformed Infrared spectroscopy (ATR-FTIR). Secondary structure, conformational changes, interactions with lipids and spatial positioning of membranes, proteins and peptides are commonly analyzed by this method that allows having a simultaneous vision of the membrane and the protein that is bound. In particular, ATR-FTIR is especially advantageous to evaluate the membrane lipids order and the effective position of a protein relative to the membrane. This technique has been successfully applied to study alpha-helical peptides and proteins, and also beta-sheet, beta-barrel and beta-sandwich proteins, but potentially it could be applicable for any protein structure suitable for a geometric approximation. The present review wants to examine and summarize the different models developed to calculate the orientation of these proteins giving some practical examples, analyzing lipid alignment, protein secondary structure and orientation.